Decoding Authenticity In Digital Marketing: A Netnographic Study Of User-Generated Content, Algorithmic Curation, And Brand Storytelling On @Scarlettofficial - Rofian Dedi Susanto; Rifky Maulana (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2026)
This research explores the intersection of algorithmic curation and brand authenticity on Instagram, focusing on @scarlettofficial. In a digital landscape governed by engagement-driven algorithms, brands face a tension between high-fidelity production and consumer demand for unvarnished authenticity. Utilizing a netnographic approach (July–September 2025) and grounded theory analysis, this study investigates how the strategic deployment of low-fidelity User-Generated Content (UGC) serves as a structural bridge to bypass algorithmic gatekeeping. Findings reveal that @scarlettofficial navigates the